1996
DOI: 10.1080/02688699646907
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous lumbar and intraventricular manometry to evaluate the role and safety of lumbar puncture in raised intracranial pressure following subarachnoid haemorrhage

Abstract: We report a prospective investigation of a bedside test to evaluate the role and safety of lumbar puncture in raised intracranial pressure in patients with subarachnoid haemorrhage. Fourteen patients who underwent aneurysm clipping following subarachnoid haemorrhage were studied. All patients had intraventricular drains and needed high volume cerebrospinal fluid (CSF) drainage to maintain the normal intracranial pressure. A lumbar puncture was performed in these patients and the simultaneous opening lumbar and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 4 publications
0
9
0
2
Order By: Relevance
“…17 A previously reported comparison of simultaneous lumbar and ventricular pressure in this setting demonstrated that both pressure readings reflect each other closely. 18 Drainage of 5 to 20 mL of CSF through a lumbar drain has been shown to approximately halve ICP in patients with aSAH and those with brain injury. 19 Additional benefits observed included an improvement in regional cerebral blood flow and brain tissue oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…17 A previously reported comparison of simultaneous lumbar and ventricular pressure in this setting demonstrated that both pressure readings reflect each other closely. 18 Drainage of 5 to 20 mL of CSF through a lumbar drain has been shown to approximately halve ICP in patients with aSAH and those with brain injury. 19 Additional benefits observed included an improvement in regional cerebral blood flow and brain tissue oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the technique, ICP measuring can be undertaken in different intracranial anatomical locations: intraventricular, intraparenchymal, epidural, subdural, and subarachnoidal. Additionally, in patients with communicating CSF pathways, ICP may under certain circumstances be assessed by lumbar puncture [26, 27, 42, 43], as mentioned in the above chapter.…”
Section: Invasive Methods Of Measuring Icpmentioning
confidence: 99%
“…Additionally, in patients with subarachnoid hemorrhage or spontaneous ganglionic hemorrhage, the true intracranial pressure may be estimated by lumbar cerebrospinal fluid pressure [26, 27]. …”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies in a small number of patients demonstrated a significant reduction of increased ICP in response to controlled lumbar CSF drainage without any signs of cerebral herniation. 1,10,19,21,39 In researching this issue, we have demonstrated a significant reduction in ICP by using controlled lumbar CSF drainage according to defined indications in 23 patients with either TBI or SAH. 28 Signs of herniation were observed temporarily in 2 patients in that series.…”
mentioning
confidence: 99%